Perlindungan Hukum Terhadap Notaris dari Pembuatan Akta Pernyataan Keputusan Rapat Terkait Notulen Rapat Umum Pemegang Saham Yang Dipalsukan - Bambang Yudianto; Felicitas Sri Marniati; Putra Hutomo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Pursuant to Article 16 Paragraph (1) Letter a of Law Number 2 of 2014 Concerning the Position of Notary Public which emphasizes the obligation of a notary to act in a trustworthy, honest, thorough, independent, impartial and safeguarding the interests of the parties involved in legal actions, however in practice sometimes it is used by appearers by falsifying the minutes of the GMS so that the notary becomes the suspected perpetrator of a crime. The formulation of the problem in this study is what are the legal consequences of the deed of meeting decision statements related to the falsified GMS minutes. The method used in this research is normative juridical research in the form of library law materials or secondary data with sources of primary, secondary and tertiary legal materials. The research approach used is statutory, conceptual, analytical and case approaches as well as legal material analysis techniques carried out with systematic and grammatical legal interpretations. The results of the study show that the legal consequences of the deed of meeting decision regarding the falsified GMS minutes resulted in the deed becoming null and void and the aggrieved parties had to file a civil suit to the court to cancel the deed. In this case the notary cannot be held criminally responsible if a loss arises for one of the parties, because the deed is a partij acte which is entirely based on the statements and statements of the parties which are already in draft form, the notary only writes it into an authentic deed, so the minutes of the GMS are falsified be the responsibility of the appearers.